EPICURE, MARX AND RELIGION’S CRITICISM: SOME NOTES - Venancio, Romero (Religare: Revista do Programa de Pós-Graduação em Ciências das Religiões da UFPB, 2016)
Our work aims to present Marx’s reading of Epicure work and the meaning of this “first materialism” to the German thinker. Our introductory work is divided in this way: a brief commentary on Epicure’s life and philosophy followed by a presentation of Marx’s analysis about Epicure on his doctorship’s initial work.